The Spectroscopic Behaviour of Rhodamine 6G in Liquid and Solid Solutions - Baghdad Science Journal (مجلة بغداد للعلوم, 2008)
Absorption, fluorescence, quantum yield and lifetime of rhodamine 6G in chloroform, methanol and dimethyl sulfoxide were measured. From a comparison of these quantities, with those for solid solutions (solid solutions are obtained by mixing constant volume proportions of dye at a concentration of 1*10-4M/l with different volume proportions from the concentrated solution of polymer in chloroform and dimethyl sulfoxide). The results showed that the addition of polymer to liquid concentrated solutions (1*10-4M/l )of rhodamine 6G dye from expecting [which leading to development active medium for laser dye at high concentration] increase the spectra shift toward high energies, and the luminescence quantum yield but decreasing radiative lifetime.